(untitled) (Philological Studies, 2019)
Most of Macedonian population lived in unhygienic conditions, which was the cause for many diseases. Illiterate population sought their remedy in folk medicine. Macedonian leaders of the National Revival and physicians greatly contributed to raising the population’s awareness. With their activities and manner of curing they helped the population to overcome their stuffiness.